2004
DOI: 10.1038/sj.ejcn.1601931
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic gastric emptying in protein energy malnutrition: effect of type of meal and nutritional recovery

Abstract: Objective and Design: The earlier reports of disturbed gastric motility in protein energy malnutrition (PEM) point out to its possible contribution in the difficulties faced during nutritional rehabilitation. This study was thus designed to assess the ultrasonographic gastric emptying time (GET) using 20 ml/kg body weight of both liquid and semisolid meals, in 27 patients suffering from PEM as well as in 15 healthy matching infants to delineate any defect present, its degree in different types of PEM and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
5
10
0
Order By: Relevance
“…Although some studies have suggested that changes are not seen until 22 weeks of nutritional rehabilitation, 11 others have reported that gastric emptying improves after 30 ± 7 days. 45 Given the variable time courses reported in the liter-ature, we chose an interval of 14 ± 2 weeks for repeat testing, given that it may take up to 3 months of treatment to begin to establish consistent weight recovery in AN. 46 Thus, long-term follow-up might reveal different results that those reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested that changes are not seen until 22 weeks of nutritional rehabilitation, 11 others have reported that gastric emptying improves after 30 ± 7 days. 45 Given the variable time courses reported in the liter-ature, we chose an interval of 14 ± 2 weeks for repeat testing, given that it may take up to 3 months of treatment to begin to establish consistent weight recovery in AN. 46 Thus, long-term follow-up might reveal different results that those reported here.…”
Section: Discussionmentioning
confidence: 99%
“…56 Gastrointestinal dysfunction occurs frequently in Parkinson disease and it is now recognized that abnormalities of gastrointestinal motor function (especially constipation) precede the typical features of Parkinson disease. 57 Involvement of the dorsal motor nucleus of the vagus may influence parasympathetic innervation, whereas abnormalities of the enteric nervous system itself (eg, Lewy bodies and loss of dopaminergic neurons) are also evident.…”
Section: Medical Conditions and Medications Associated With Delayed Gmentioning
confidence: 99%
“…Additionally Shaaban et al. [2] did not report any harm occurring to their PEM patients from the prolonged GET.…”
Section: Introductionmentioning
confidence: 99%